THE IMPACT OF TRANSLATION ON FOREIGN LANGUAGE LEARNING - Dilshodakhon Muminova (Web of Journals Publishing, 2025)
The significance of this approach in instructing students is extensively discussed in this article, as is the function that translation plays in learning a foreign language, as well as its efficacy as a method of language acquisition.
Keywords: Original text, translation practice, translation pedagogy, education and language, methodology, and contemporary approaches.